2007
DOI: 10.1080/13632750601135907
|View full text |Cite
|
Sign up to set email alerts
|

Drug use amongst young people attending emotional and behavioural difficulty units during adolescence: a longitudinal analysis

Abstract: This paper reports on the findings from a longitudinal survey of the drug use behaviours of young people who were attending Emotional and Behavioural Difficulty (EBD) units from the age of 11-16 years. It forms part of the Belfast Youth Development Study, a longitudinal study of adolescent drug use. This paper presents a follow-up report to a cross-sectional paper that reported on drug use behaviours of a sample of young people attending EBD units when aged 12-13 years at school (Year 9). In the present paper,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The design and development of this instrument is reported elsewhere (for example, McCrystal, Percy, & Higgins, 2007c). In this paper, use of licit substances (i.e.…”
Section: The Measuring Instrumentmentioning
confidence: 99%
“…The design and development of this instrument is reported elsewhere (for example, McCrystal, Percy, & Higgins, 2007c). In this paper, use of licit substances (i.e.…”
Section: The Measuring Instrumentmentioning
confidence: 99%
“…Other common patterns were noted amongst each high risk group of young people regardless of their school status. For example, the high risk samples were more likely to be male, live in a disrupted family, report indicators of social deprivation and attend non-grammar schools (in Northern Ireland academic ability remains the main selection criteria for grammar schools) (McCrystal et al, 2007a(McCrystal et al, , 2007b.…”
Section: Cannabis Use Amongst the High Risk Booster Sample Of The Bydsmentioning
confidence: 99%
“…There were bundles of reports that evidenced that using drugs for nonmedical purposes causes addiction and drug dependence, which is mainly responsible for causing serious epidemiological diseases and disturbing quality of life ( Organization, 2010 , Siriwatanamethanon et al, 2012 ). However, the most cited factors for illicit drugs among the students were emotional immaturity, lack of self-esteem, poor interest in education or schooling, and a bad relationship with their parents ( McCrystal et al, 2007 , Zhuravleva, 2001 ). A recent report from different college students published in September 2020 revealed that the majority of the students were influenced by their friends to abuse drugs followed by curiosity to use, search for fun, or overcome school-related stress to overcome family-related issues and media influence also it was evidenced that most commonly abused drug was marijuana comparing to other illicit drugs ( Arria et al, 2017 ; J. E. Schulenberg et al, 2021 , Welsh et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%